MODEL MATEMATIS PREDIKSI KESUKSESAN PRODUK MEMPERTIMBANGKAN BUDAYA PADA KENDARAAN BERMOTOR RODA EMPAT - Ratih Setyaningrum; Subagyo Subagyo; Andi Rahadiyan Wijaya (Universitas Gadjah Mada, 2015)
Cultural aspects and Maslow needs has been considered on product development process. There is also has indication of product selection mutation based on Maslow needs ability. Based on these conditions, formulation of successful product development strategy in the future need to consider cultural aspects. Therefore, the purpose of this study is to determine mathematical model of products four-wheeled vehicles and to predict success. Stages of research include developing mathematical models, the validation process models and best model selection. The results of a mathematical model based on market share indicates that the component must-be inversely proportional to the success of the product, while the components of one-dimentional and attractive is directly proportional to the success of the product. The calculation result that Kano generate mathematical equations require further research. These research expected can determine the success of the model with the parameters of the success product in addition to market share.